From the solution of the expression, it can be seen that s = 6 when t = 3 while t = 1 when s = 2.
<h3>How do we solve a mathematical expression?</h3>
Given:
(12t) = (6s) ........................ (1)
When t = 3, we can solve for s from the expression in equation (1) by substituting t = 3 into the equation as follows:
12 * 3 = 6s
36 = 6s
s = 36 / 6
s = 6
When s = 2, we can solve for t from the expression in equation (1) by substituting s = 2 into the equation as follows:
12t = 6 * 2
12t = 12
t = 12 / 12
t = 1
Learn more about mathematical expression here: brainly.com/question/12401681.
#SPJ1
Answer:
5. 3/10
6. 7/12
7. 7/8
8. 4/3
Step-by-step explanation: Hope this helps!
1. figure c
2.figure b
3. figure a b and c
I believe the answer would be 10,860 my friend :) good luck with your problem, and have a great day